5α-Reductase type 1 deficiency or inhibition predisposes to insulin resistance, hepatic steatosis, and liver fibrosis in rodents - Livingstone, Dawn E W; Barat, Pascal; Di Rollo, Emma M; Rees, Georgina A; Weldin, Benjamin A; Rog-Zielinska, Eva A; MacFarlane, David P; Walker, Brian R; Andrew, Ruth (Diabetes (New York, N.Y.), 2015)
5α-Reductase type 1 (5αR1) catalyses A-ring reduction of androgens and glucocorticoids in liver, potentially influencing hepatic manifestations of the metabolic syndrome. Male mice, homozygous for a disrupted 5αR1 allele (5αR1 knockout [KO] mice), were studied after metabolic (high-fat diet) and fibrotic (carbon tetrachloride [CCl4]) challenge. The effect of the 5α-reductase inhibitor finasteride on metabolism was investigated in male obese Zucker rats. While eating a high-fat diet, male 5αR1-KO mice demonstrated greater mean weight gain (21.6 ± 1.4 vs 16.2 ± 2.4 g), hyperinsulinemia (insulin area under the curve during glucose tolerance test 609 ± 103 vs. 313 ± 66 ng ⋅ mL(-1) ⋅ min), and hepatic steatosis (liver triglycerides 136.1 ± 17.0 vs. 89.3 ± 12.1 μmol ⋅ g(-1)). mRNA transcript profiles in liver were consistent with decreased fatty acid β-oxidation and increased triglyceride storage. 5αR1-KO male mice were more susceptible to fibrosis after CCl4 administration (37% increase in collagen staining). The nonselective 5α-reductase inhibitor finasteride induced hyperinsulinemia and hepatic steatosis (10.6 ± 1.2 vs. 7.0 ± 1.0 μmol ⋅ g(-1)) in obese male Zucker rats, both intact and castrated. 5αR1 deficiency induces insulin resistance and hepatic steatosis, consistent with the intrahepatic accumulation of glucocorticoids, and predisposes to hepatic fibrosis. Hepatic steatosis is independent of androgens in rats. Variations in 5αR1 activity in obesity and with nonselective 5α-reductase inhibition in men with prostate disease may have important consequences for the onset and progression of metabolic liver disease.